Simulation analysis of the effect of temperature on overpotentials in PEM electrolyzer system / Abdul Hadi Abdol Rahim, Alhassan Salami Tijani and Farah Hanun Shukri - Abdol Rahim, Abdul Hadi; Salami Tijani, Alhassan; Shukri, Farah Hanun (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
Mass transport through the porous electrode of Polymer Electrolyte Membrane (PEM) electrolyzer encounters a resistance when it flows through the electrodes. As the resistance increases with increasing flow, some energy is loss in the process which causes diffusion overvoltage. The cell voltage to be imposed is higher because of mass transport limitations. In PEM electrolyzer, the cell voltage is generally the sum of reversible voltage and the overpotentials. The ohmic, activation and mass transfer losses are the most prominent losses in a PEM electrolyser. In this manuscript, mathematical models related to PEM electrolyzer based on a combination of thermodynamics fundamental and electrochemical relations are presented. A single cell simple PEM electrolyzer is analyzed on the basis ofwell-known Butler- Volmer kinetic for electrodes and transport resistance in the polymer-electrolyte. In addition, the overpotential at the anode, cathode and overpotential due to ohmic resistances are analyzed as well. Then, the effect of temperature on operating cell voltage, resistance and ionic conductivity of the polymer electrolyte are examined with the developed model. Finally sensitivity analysis for different values of exchange current densities at anode and cathode are tested. The simulation results indicated that as temperature increases, there is a significant or sharp decrease in ohmic resistance from 0.198Ω/cm² at 40°C to 0.125Ω/ cm² at 80°C. Also at 40°C and2A/ cm², an operating voltage of 2.13 V has seen achieved, however at higher temperature (80°C), the operating cell voltage drops to 1.98V at 2A/ cm² and this constitutes about 7% reduction in operating cell voltage. From this observation it can be concluded that the ionic conductivity of the membrane assembly increases with temperature.